One year results of the Middlesbrough early revascularisation to limit infarction (MERLIN) trial. Issue 10 (14th September 2005) - Sutton, A G C; Campbell, P G; Graham, R; Price, D J A; Gray, J C; Grech, E D; Hall, J A; Harcombe, A A; Wright, R A; Smith, R H; Murphy, J J; Shyam-Sundar, A; et al.
Abstract : Objective: To report one year results of the MERLIN (Middlesbrough early revascularisation to limit infarction) trial, a prospective randomised trial comparing the strategy of coronary angiography and urgent revascularisation with conservative treatment in patients with failed fibrinolysis complicating ST segment elevation myocardial infarction (STEMI). The 30 day results have recently been published. At the planning stage of the trial, it was determined that follow up of trial patients would continue annually to three years to determine whether late benefit occurred. Subjects: 307 patients who received a fibrinolytic for STEMI but failed to reperfuse early according to previously described ECG criteria and did not develop cardiogenic shock. Methods: Patients were randomly assigned to receive either emergency coronary angiography with a view to proceeding to urgent revascularisation (rescue percutaneous coronary intervention (rPCI) arm) or continued medical treatment (conservative arm). The primary end point was all cause mortality at 30 days. The secondary end points included the composite end point of death, reinfarction, stroke, unplanned revascularisation, or heart failure at 30 days. The same end points were evaluated at one year and these results are presented. Results: All cause mortality at one year was similar in the conservative arm and the rPCI arm (13.0% v 14.4%, p = 0.7, risk difference (RD) −1.4%, 95% confidence interval (CI) −9.3 to 6.4). The incidence of the composite secondary end point of death, reinfarction, stroke, unplanned revascularisation, or heart failure was significantly higher in the conservative arm (57.8% v 43.1%, p = 0.01, RD 14.7%, 95% CI 3.5% to 25.5%). This was driven almost exclusively by a significantly higher incidence of subsequent unplanned revascularisation in the conservative arm (29.9% v 12.4%, p < 0.001, RD 17.5%, 95% CI 8.5% to 26.4%). Reinfarction and clinical heart failure were numerically, but not statistically, more common in the conservative arm (14.3% v 10.5%, p = 0.3, RD 3.8%, 95% CI −3.7 to 11.4, and 31.2% v 26.1%, p = 0.3, RD 5.0%, 95% CI −5.1 to 15.1). There was a strong trend towards fewer strokes in the conservative arm (1.3% v 5.2%, p = 0.06, RD −3.9%, 95% CI −8.9 to 0.06). Conclusion: At one year of follow up, there was no survival advantage in the rPCI arm compared with the conservative arm. The incidence of the composite secondary end point was significantly lower in the rPCI arm, but this was driven almost entirely by a highly significant reduction in the incidence of further revascularisation.